2020
DOI: 10.1016/j.dld.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Can a transition clinic bridge the gap between paediatric and adult inflammatory bowel disease care models?

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 80 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…Many previous studies have identified various barriers to a seamless transfer of care, as shown in Table 1 [5, 13, 16, 18, 19, 27]. These cover a range of specialists such as healthcare providers, patients, guardians, and social systems and may be single or multiple.…”
Section: Barriers To Successful Transitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many previous studies have identified various barriers to a seamless transfer of care, as shown in Table 1 [5, 13, 16, 18, 19, 27]. These cover a range of specialists such as healthcare providers, patients, guardians, and social systems and may be single or multiple.…”
Section: Barriers To Successful Transitionmentioning
confidence: 99%
“…One of the ideal models for support of patients with childhood-onset IBD during the transition period is to implement an outpatient-based transitional care clinic run by a multidisciplinary team [27]. Although there is no common definition of a transition clinic and the settings are notably heterogeneous [17], a multidisciplinary approach and good interaction among the various stakeholders are potential keys of the success of transition [5]. In some circumstances, it may be difficult to set up a transitional clinic in some institutions due to territorial dispersion (regional specifics) or lack of medical resources.…”
Section: Joint Clinic and Alternative Visitmentioning
confidence: 99%
See 3 more Smart Citations